Nümunehâyi ez-Istılahat-ı maarif-i islami be-Arabi ve Farsi ve Muadil Anha der-Zeban-ı Frarsa = Examples of arabc and Persian Terms of Islamic teachings and their equivalents in French - Hasan Habîbî. (Tahran)
3+45+1 s.